Political-Military Corruption and Military Performance in Extra-State Wars through Security Governance - Nathan Decety (UIN Sunan Gunung Djati, 2026)
Corruption weakens the political and institutional foundations through which states organize, control, and deploy military power. In extra-state wars, the conventional states often possess material advantages that do not automatically translate into effective military performance. This study aims to examine how political-military corruption shapes state performance in extra-state wars through the lens of security governance. The study uses a quantitative explanatory design based on historical conflict and governance datasets. The main unit of analysis is the state-war observation in extra-state wars recorded by the Correlates of War dataset. Corruption is measured through political corruption and regime corruption indicators, while military performance is examined through war outcomes, loss exchange ratios, and war duration. The analysis uses logistic regression for war outcomes and ordinary least squares regression for logged loss ratios and logged war duration. The principal findings show that corruption is more clearly associated with defeat and higher relative losses than with conflict duration. The study concludes that corruption weakens military performance by damaging the governance mechanisms that convert material resources into effective military action. This article contributes to political science by linking corruption, security governance, state capacity, and civil-military control to the study of military performance.